PESAN DAN MAKNA KARIKATUR BREXIT PATRIC CHAPPATTÉ - Latjuba, Ade Yolanda; Savitri Mustar, Adel; Hasyim, Muhammad (Universitas Hasanuddin, 2021)
This research comes from a political caricature by Patrick Chappatté in French and discusses about the Brexit issue that occurred in Great Britain. A caricature is an art in the form of an illustration with the main object being a human face. Caricature aims to provide an information or to criticize something. The purpose of this study is to explain the description of the issue of Brexit and to analyze the message and the meaning to be conveyed using a semiotic approach. This reaserch use descriptive qualitatuve approach. The results of this study found that the description of the issue regarding Brexit illustrates the efforts made by the Prime Minister to fight for the votes of the majority of the people who want to Brexit, while the meaning conveyed through the caricature is how the struggle, process, and drama faced by Great Britain in order to leave the European Union.